12(t-6)+6t=6(3t+4)-9

Simple and best practice solution for 12(t-6)+6t=6(3t+4)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(t-6)+6t=6(3t+4)-9 equation:


Simplifying
12(t + -6) + 6t = 6(3t + 4) + -9

Reorder the terms:
12(-6 + t) + 6t = 6(3t + 4) + -9
(-6 * 12 + t * 12) + 6t = 6(3t + 4) + -9
(-72 + 12t) + 6t = 6(3t + 4) + -9

Combine like terms: 12t + 6t = 18t
-72 + 18t = 6(3t + 4) + -9

Reorder the terms:
-72 + 18t = 6(4 + 3t) + -9
-72 + 18t = (4 * 6 + 3t * 6) + -9
-72 + 18t = (24 + 18t) + -9

Reorder the terms:
-72 + 18t = 24 + -9 + 18t

Combine like terms: 24 + -9 = 15
-72 + 18t = 15 + 18t

Add '-18t' to each side of the equation.
-72 + 18t + -18t = 15 + 18t + -18t

Combine like terms: 18t + -18t = 0
-72 + 0 = 15 + 18t + -18t
-72 = 15 + 18t + -18t

Combine like terms: 18t + -18t = 0
-72 = 15 + 0
-72 = 15

Solving
-72 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 0=8x^2-6x-14 | | 7a^2+2a=0 | | 26=3m-7m | | 2(x-7)=8 | | 1+5x=-15+x | | 0=2x^2+x-1 | | -4-2n+3n=4-n | | -12+x=2x+3x | | 5a^2+9a-2= | | 1+3+6x-8=4x+1+7 | | -4x+8=20 | | x^2+36-144=0 | | 6m^2-5m=14 | | 83.3*(0.01)= | | 0.4x-0.2(3-x)=1.8 | | 2b+10=b+4 | | 9-10x-5-4x=6 | | 10c^2+33c-54=0 | | A^5*6a^3=y | | 5x^0y^1= | | (x+1)+(x-1)=e^4 | | .5(10-9x)=1.25 | | .5(10-9x)=.125 | | 8c-1200=5c | | 56765x+68-79=9865 | | 9-17x-5-4x=7 | | -x-8+14x=34 | | 3x+1y=21 | | 4-0.9k=4 | | 1x+2y=12 | | 3n^2-8n+5= | | -4(5+7y)+6(2y-9)= |

Equations solver categories